Heritage management fund guarantee: Concept and experiences - LIJING, ZHANG; ALBATTAT, AHMAD (International Journal of Multidisciplinary Research and Studies, 2024)
A successful heritage management is highly dependent on the fund guarantee that supports the cultural heritage in any phases both in construction and maintenance for sustainable protection of the heritage. This article focuses on Heritage Management Fund Guarantee practice in several countries especially those that conducted a favorable result, such as the USA, Italy, the UK, and Japan. Their experiences provide insights into how funds guarantee heritage management both in public funding and non-public funding. Also, some actions they conducted related to national parks indeed offer a reference for China in terms of the huge project of national culture parks as the main heritage management practice in China recently. Particularly, this paper presents the concept of fund guarantee for heritage management. Then, the source of funds guarantee for heritage management is discussed, namely public funding of the governments and non-public capital investment. Public funding includes state investment, local government investment, and tax relief, while non-public investment involves international heritage assistance, corporate and private investment, and income from the operation of heritage sites. Later, the measures and experiences of heritage management fund guarantee are analyzed. multi-channel funding has been formed internationally, with financial allocations from national and local governments mainly, supplemented by other channels like foundations and enterprises.